Nomograms for calculating the safety factor of homogeneous earth dams in long-term stability - Rida Lakehal; Lakhdar Djemili; Larbi Houichi (African Journal of Environmental Economics and Management, 2019)
The slope stability analysis is routinely performed by engineers to evaluate the stability of embankment dams, road embankments, river training works, excavations and retaining walls. To ensure the geotechnical safety of the dam, the slope of embankment must be correctly designed and constructed. In this work, by applying the modified method of Bishop, an attempt was made to construct sets of nomgrams for the calculation of the safety factor of homogeneous earth dams under long term stability, which allow the user to get the optimal safety factor of the dam, immediately, according the material classification and the parameters of design, height and slope.